Business Process Oriented Knowledge Management System Design (Case Study Development Center of Metrological Human Resources, Ministry of Trade Republic of Indonesia) - Febriantoro, Wicaksono; Surendro, Kridanto (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. The aim of this study is to design a business process oriented Knowledge Management System (KMS) in government training institutions using knowledge modeling methods and knowledge infrastructure process design of Strohmaier. Lecturer (WI) business process is the main case study for this research. The preliminary identification and analysis showed that 7 of 10 business processes have not been fully identified in terms of their knowledge processes. Further analysis showed that in general, all business processes have not been optimized yet to fulfill all the components of knowledge creation to knowledge application. The results of the completed knowledge process design showed that there are 53 stages of the process (there are new additional 19 stages of the process). The new processes are largely on the knowledge transfer and knowledge application that have been defined. In addition, KMS architecture and IT tools as supporting knowledge infrastructure designs are defined. The IT tools are expected to support two knowledge process strategies :the codification strategy with the supporting IT Tools : content management system , information retrieval system, expert locator and the personalization strategy with the supporting IT Tools such as community of practice tool, virtual work space application and discussion group based application.Keywords: business processes, knowledge process, knowledge management system, knowledge infrastructure, IT Tools